Complete PSA Remission without Adjuvant Therapy after Secondary Lymph Node Surgery in Selected Patients with Biochemical Relapse after Radical Prostatectomy and Pelvic Lymph Node Dissection - Alexander Winter; Jens Uphoff; Rolf-Peter Henke; Friedhelm Wawroschek (Advances in Urology)
Introduction. To evaluate whether secondary resection of lymph node (LN) metastases (LNMs) can result in PSA remission, we analysed the PSA outcome after resection of LNM detected on PET/CT in patients with biochemical failure. Materials and Methods. 11 patients with PSA relapse (mean 3.02 ng/mL, range 0.5–9.55 ng/mL) after radical prostatectomy without adjuvant therapy were included. Suspicious LN (1–3) detected on choline PET/CT and nearby LN were openly dissected (09/04–02/11). The PSA development was examined. Histological and PET/CT findings were compared. Results. 9 of 10 patients with histologically confirmed LNM showed a PSA response. 4 of 9 patients with single LNM had a complete permanent PSA remission (mean followup 31.8, range 1–48 months). Of metastasis-suspicious LNs (14) 12 could be histologically confirmed. The additionally removed 25 LNs were all correctly negative. Conclusions. The complete PSA remissions after secondary resection of single LNM argue for a feasible therapeutic benefit without adjuvant therapy. For this purpose the choline PET/CT is in spite of its limitations currently the most reliable routinely available diagnostic tool.